2014
DOI: 10.1080/02699931.2014.901213
|View full text |Cite
|
Sign up to set email alerts
|

Automatic control of negative emotions: Evidence that structured practice increases the efficiency of emotion regulation

Abstract: Emotion regulation (ER) is vital to everyday functioning. However, the effortful nature of many forms of ER may lead to regulation being inefficient and potentially ineffective. The present research examined whether structured practice could increase the efficiency of ER. During three training sessions, comprising a total of 150 training trials, participants were presented with negatively valenced images and asked either to “attend” (control condition) or “reappraise” (ER condition). A further group of partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 43 publications
1
35
0
Order By: Relevance
“…This could indicate that employees may habituate to the frequent use of surface acting strategies, thus experiencing reduced emotional dissonance and physiological reactivity to frequent conflict. These finding support and extend prior research that identified reduced reactivity associated with frequently used emotional regulation (Chirstou-Champi, et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This could indicate that employees may habituate to the frequent use of surface acting strategies, thus experiencing reduced emotional dissonance and physiological reactivity to frequent conflict. These finding support and extend prior research that identified reduced reactivity associated with frequently used emotional regulation (Chirstou-Champi, et al, 2015).…”
Section: Discussionsupporting
confidence: 89%
“…For employees who regulate emotions in response to frequent interpersonal conflicts at work, the frequent engagement in both conflict and surface acting may over time limit the incremental increases in negative impact that such engagement has on heightened emotional dissonance and physiological reactivity. Prior research indicates that practicing emotional regulation strategies can decrease the effort required and increase habituation (Chirstou-Champi, Farrow, & Webb, 2015). Further, emotional regulations strategies have been associated with reduced physiological reactivity when the strategies were unconsciously used (Williams, Bargh, Nocera, & Gray, 2009).…”
Section: Interpersonal Conflict and Emotional Labourmentioning
confidence: 99%
See 1 more Smart Citation
“…Such habitual strategies may be elicited automatically when dealing with undesired emotions [29]. The formation of emotion regulation habits may thus render the stage of strategy selection implicit, such that people can move directly to enacting the emotion regulation strategy (which we discuss in the next section), without the need for deliberation about how to regulate emotions.…”
Section: Strategy Selectionmentioning
confidence: 99%
“…People's emotion-regulatory skills are presumably grounded in early interaction experiences with caregivers [40]. Nevertheless, the ability to regulate emotions continues to improve throughout the lifespan [41] and an experiment by Christou-Champi et al [29] showed that short practice sessions over three days can improve emotion regulation two weeks later. Thus, training may be an important way to improve the implementation of emotion regulation strategies.…”
Section: Enacting the Strategymentioning
confidence: 99%